Immature astrocytes promote CNS axonal regeneration when combined with chondroitinase ABC - Filous, Angela R. (2010)
Regeneration of injured adult CNS axons is inhibited by formation of a glial scar. Immature astrocytes are able to support robust neurite outgrowth and reduce scarring, therefore, we tested whether these cells would have this effect if transplanted into brain injuries. Utilizing an in vitro spot gradient model that recreates the strongly inhibitory proteoglycan environment of the glial scar we found that, alone, immature, but not mature, astrocytes had a limited ability to form bridges across the most inhibitory outer rim. In turn, the astrocyte bridges could promote adult sensory axon re-growth across the gradient. The use of selective enzyme inhibitors revealed that MMP-2 enables immature astrocytes to cross the proteoglycan rim. The bridge-building process and axon regeneration across the immature glial bridges were greatly enhanced by chondroitinase ABC pre-treatment of the spots. We used microlesions in the cingulum of the adult rat brains to test the ability of matrix modification and immature astrocytes to form a bridge for axon regeneration in vivo. Injured axons were visualized via p75 immunolabeling and the extent to which these axons regenerated was quantified. Immature astrocytes co-injected with chondroitinase ABC induced axonal regeneration beyond the distal edge of the lesion. However, when used alone, neither treatment was capable of promoting axonal regeneration. Our findings indicate that when faced with a minimal lesion, neurons of the basal forebrain can regenerate in the presence of a proper bridge across the lesion and when levels of chondroitin sulfate proteoglycans (CSPGs) in the glial scar are reduced.